Effects of resistance training on osteosarcopenia in community-dwelling postmenopausal Korean women: Randomised controlled ERTO-K trial - Byung Chan Lee; Kyung Il Kim; Juhyun Lee; Kang Hee Cho; Changwon Moon (Experimental Gerontology)
Objective: We evaluated the efficacy of a 6-month progressive resistance exercise in postmenopausal women with osteosarcopenia. Study design: Thirty-four community-dwelling postmenopausal women with osteosarcopenia were randomly assigned to either a resistance exercise group (RE; n = 17) or a home exercise group (HE; n = 17). Both groups received home exercise brochures and nutritional supplementation. The RE group additionally participated in supervised resistance training sessions twice weekly. Main outcome measures: The primary outcome was the change in the skeletal muscle index (SMI) and bone mineral density (BMD). The secondary outcomes included changes in handgrip strength (HGS) and physical performance. Results: Seventeen and sixteen participants in the RE and HE groups, respectively, completed the intervention. The RE group showed significantly greater SMI improvement at the 12-week follow-up (0.310 ± 0.343 kg/m2 vs. 0.011 ± 0.423 kg/m2 in HE). However, there was no significant difference between groups at the 24-week follow-up. The other primary outcome, BMD, did not show any statistically significant differences either within or between groups. While both groups showed significant improvement in HGS and physical performance over time, the RE group had significantly higher HGS at the 6-week and 18-week follow-ups. Conclusions: A 6-month program of progressive resistance exercise combined with nutritional support improved muscle mass and strength in postmenopausal women with osteosarcopenia. Although the HE group showed less improvement at earlier time points, their muscle strength and physical performance were comparable to those of the RE group by the end of the intervention.